2015
DOI: 10.1530/edm-15-0062
|View full text |Cite
|
Sign up to set email alerts
|

Severe paraneoplastic hypoglycemia secondary to a gastrointestinal stromal tumour masquerading as a stroke

Abstract: SummaryWe report the case of a 70-year-old previously healthy female who presented acutely to the Accident and Emergency department with left-sided vasomotor symptoms including reduced muscle tone, weakness upon walking and slurred speech. Physical examination confirmed hemiparesis with VIIth nerve palsy and profound hepatomegaly. A random glucose was low at 1.7 mmol/l, which upon correction resolved her symptoms. In hindsight, the patient recalled having had similar episodes periodically over the past 3 month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…It is unlikely that hypothyroid influenced the hypoglycemia in our case because the hypothyroid was latent. Therefore, we next suspected NICTH due to GIST, although GIST related-NICTH is very rare [ 13 - 16 ]. As expected, additional immunohistochemical staining with an anti-IGF-2 antibody of the resected tumor tissues was positive, which strongly suggested GIST related-NICTH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unlikely that hypothyroid influenced the hypoglycemia in our case because the hypothyroid was latent. Therefore, we next suspected NICTH due to GIST, although GIST related-NICTH is very rare [ 13 - 16 ]. As expected, additional immunohistochemical staining with an anti-IGF-2 antibody of the resected tumor tissues was positive, which strongly suggested GIST related-NICTH.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that steroid therapy is beneficial for the prevention of hypoglycemia by NICTH [ 5 , 13 , 14 , 20 ]. We decided to administer the steroid despite the fact that our patient had chronic hepatitis B, for which steroid could affect the reactivation, because the HBV-PCR had been inhibited to the value below the detection limit likely due to continuous entecavir therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the great majority of endocrine PNS produced from non-endocrine neoplasms are found in highly malignant tumours mainly involving the lungs, breasts, prostate, ovaries, skin, colon and certain forms of haematological malignancies; however, tumours arising from virtually any tissue have been implicated, albeit rarely (Lorch et al 2007, Nimalasena et al 2008, Gilmore et al 2009, Nella et al 2014, Dimitriadis et al 2015, Thajudeen et al 2016.…”
Section: Paraneoplastic Endocrine Syndromesmentioning
confidence: 99%
“…Tumour autoimmune hypoglycaemia may also occur secondary to insulin receptor auto-antibody production, whereas excessive tumour burden with glucose consumption, massive tumour liver infiltration, and pituitary or adrenal gland destruction by the tumour are the other mechanisms in cases of large and aggressive neoplasias (Iglesias & Diez 2014). Non-islet cell tumour hypoglycaemia (NICTH) presents as recurrent or constant hypoglycaemic episodes and mostly affects elderly patients with advanced tumours (Teale & Wark 2004, Dimitriadis et al 2015. Occasionally, these hypoglycaemic episodes can predate the diagnosis of the underlying tumour (Nayar et al 2006, Kim et al 2016.…”
Section: :6mentioning
confidence: 99%
“…Gastrointestinal stromal tumors (GISTs) are defined as stromal tumors of the gastrointestinal tract, with a spindle cell, epithelioid, or occasionally pleomorphic morphology, which are potentially malignant [ 2 ]. The predominant localization for GISTs is the stomach (60%) and small intestine (20–30%).…”
Section: Introductionmentioning
confidence: 99%